A Sensitive and Facile Assay for the Measurement of Activated Protein C Activity Levels in Vivo - Orthner, Carolyn L; Kolen, Billy; Drohan, William N (Thrombosis and Haemostasis, 1993)
Activated protein C (APC) is a serine protease which plays an important role as a naturally occurring antithrombotic enzyme. APC, which is formed by thrombin-catalyzed limited proteolysis of the zymogen protein C, functions as an anticoagulant by proteolytic inactivation of the coagulation cofactors VIIIa and Va. APC is inhibited by several members of the serpin family as well a by α2-macroglobulin. APC is being developed as a therapeutic for the prevention and treatment of thrombosis. We have developed an assay to quantify circulating levels of enzymatically active APC during its administration to patients, in healthy individuals, and in various disease states. This assay utilizes an EDTA-dependent anti-protein C monoclonal antibody (Mab) 7D7B10 to capture both APC and protein C from plasma, prepared from blood collected in an anticoagulant supplemented with the reversible inhibitor p-aminobenzamidine. Mab 7D7B10-derivatized agarose beads are added to the wells of a 96-well filtration plate, equilibrated with Tris-buffered saline, and incubated for 10 min with 200 μl of plasma. After washing, APC and protein C are eluted from the immunosorbent beads with a calcium-containing buffer into the wells of a 96-well microtiter plate containing antithrombin III (ATIII) and heparin. The amidolytic activity of APC is then measured on a kinetic plate reader following the addition of L-pyroglutamyl-L-prolyl-L-arginine-p-nitroanilide (S-2366) substrate.The rate of substrate hydrolysis was proportional to APC concentration over a 200-fold concentration range (5.0 to 1,000 ng/ml) when measured continuously over a 15 to 30 min time period. The coefficient of variation was 5.9% at 35 ng/ml and 8.8% at 350 ng/ml APC. The sensitivity of the assay could be increased by measuring the amount of color produced after longer incubation times in the endpoint mode. The measured APC activity levels were little affected by varying protein C or prothrombin over the extremes of 0 to 150% of normal plasma concentrations. By constructing the standard curve in protein C-deficient plasma, the concentration of APC activity in normal pooled plasma was determined to be 2.8 ng/ml (45 pM), which represents 0.08% of the protein C concentration. The assay was approximately 50-fold more sensitive than the identical assay, but using Mab-coated microtiter wells rather than immunosorbent beads as the capture step.